Enhanced bone defect repairing effects in glucocorticoid-induced osteonecrosis of the femoral head using a porous nano-lithium-hydroxyapatite/gelatin microsphere/erythropoietin composite scaffold. (25th January 2018) - Li, Donghai; Xie, Xiaowei; Yang, Zhouyuan; Wang, Changde; Wei, Zhun; Kang, Pengde
Abstract : Glucocorticoid-induced osteonecrosis of the femoral head (GIONFH) is a common debilitating disease that occurs in young and middle-aged adults. Abstract : Glucocorticoid-induced osteonecrosis of the femoral head (GIONFH) is a common debilitating disease that occurs in young and middle-aged adults. To treat early GIONFH, core decompression and bone graft are regarded as effective measures. However, the ideal bone graft should possess bioactivity as well as biomechanical properties. The most commonly used bone graft materials are currently unsatisfactory. In this study, we fabricated a composited scaffold using lithium (Li) to activate the Wnt signal pathway and erythrogenin (EPO) to upregulate the HIF-1/VEGF pathway to improve the osteogenic and angiogenic effects of the scaffold. We obtained the porous gelatin/nano-lithium-hydroxyapatite/gelatin microsphere/rhEPO (Li-nHA/GMs/rhEPO) composited scaffold and assessed its mechanical properties, release properties, and in vitro bioactivity. Then, we implanted the scaffold into the femoral heads of GIONFH rabbits after core decompression surgery and evaluated the osteogenic and angiogenic abilities of the scaffold in vivo as well as its bone defect repair efficacy. As the results show, the Li-nHA/GM/rhEPO scaffold possessed good mechanical compression strength and enabled continuous release of Li and rhEPO. Moreover, the scaffold improved the viability of glucocorticoid-treated BMMSCs and vascular endothelial cells and increased the expression of osteogenic and angiogenic factors. In the in vivo study, the composited scaffold improved new bone formation and exerted effects on repairing femoral head defects in GIONFH rabbits. Additionally, the osteogenic and angiogenic factors were increased along with the activation of factors in the Wnt signal pathway and the HIF-1/VEGF pathway. In conclusion, the Li-nHA/GM/rhEPO scaffold can upregulate the Wnt and HIF-1/VEGF pathways at same time and has effects on improving osteogenesis and angiogenesis, which benefits the repair of GIONFH.